PELATIHAN PERCAPAKAN BAHASA INGGRIS PESERTA DIDIK PUSAT KEGIATAN BELAJAR MASYARAKAT PERHIMPUNAN PELAJAR INDONESIA (PKBM-PPI) DI TAIWAN - Hendar Hendar; Heri Heryono; Atri Nadia Astarina; Ida Zuraida; Meita L. Sujatna (Jurnal Abdimas Bina Bangsa, 2024)
In accordance with articles 31 and 32 of the 1945 Constitution, as amended in Chapter XIII, it is stipulated that every citizen has the right to education because through education, every citizen can prepare themselves to play a role in society. This right extends to migrant workers, including all members of their families working in Taiwan, who are entitled to the same educational opportunities. Recognizing the awareness and responsibility of Indonesian students pursuing undergraduate (S1), master (S2), and doctoral (S3) studies in Taiwan to assist migrant workers in furthering their education, in 2015, they established an educational institution promoting equality in the form of a non-formal education programs, later known as the Community Learning Activity Center of the Indonesian Student Association (PKBM-PPI) Taiwan. The available programs include Package A (Elementary School), Package B (Junior High School), and Package C (Senior High School). The participants are migrant workers employed in Taiwan as caregivers for the elderly, aged between 20-50 years, predominantly female. Despite the PKBM activities commencing after their regular working hours, from 21:00 to 23:00 local time or 20:00 to 22:00 Western Indonesia Time (WIB), participants remain enthusiastic about attending the PKBM initiated and conducted by Indonesian students. This enthusiasm extends to participating in the Basic English Conversation Program, organized through collaboration between PKBM-PPI Taiwan and the Community Service Cluster of the English Language Program, Faculty of Humanities, Widyatama University, spanning one month (8 sessions).